Plant Kinases in the Perception and Signaling Networks Associated With Arthropod Herbivory - Romero-Hernandez, Gara; Martinez, Manuel (Frontiers in Plant Science, 2022)
The success in the response of plants to environmental stressors depends on the regulatory networks that connect plant perception and plant response. In these networks, phosphorylation is a key mechanism to activate or deactivate the proteins involved. Protein kinases are responsible for phosphorylations and play a very relevant role in transmitting the signals. Here, we review the present knowledge on the contribution of protein kinases to herbivore-triggered responses in plants, with a focus on the information related to the regulated kinases accompanying herbivory in Arabidopsis. A meta-analysis of transcriptomic responses revealed the importance of several kinase groups directly involved in the perception of the attacker or typically associated with the transmission of stress-related signals. To highlight the importance of these protein kinase families in the response to arthropod herbivores, a compilation of previous knowledge on their members is offered. When available, this information is compared with previous findings on their role against pathogens. Besides, knowledge of their homologous counterparts in other plant-herbivore interactions is provided. Altogether, these observations resemble the complexity of the kinase-related mechanisms involved in the plant response. Understanding how kinase-based pathways coordinate in response to a specific threat remains a major challenge for future research.